2010
DOI: 10.2215/cjn.01910310
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Expression of Kidney Injury Markers in Renal Transplant Recipients

Abstract: Background and objectives: The outcome of renal transplantation after an episode of acute rejection is difficult to predict, even with an allograft biopsy. We examined whether urinary expression of specific biomarker mRNA could be used as a noninvasive prognostic marker in kidney transplant recipients.Design, setting, participants, & measurements: We studied 63 kidney transplant recipients who require graft biopsy because of progressive worsening of kidney function. The mRNA of neutrophil gelatinase-associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
2
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 37 publications
(41 reference statements)
2
33
2
5
Order By: Relevance
“…In contrast, our previous study in kidney transplant recipients found that urinary NGAL and IL-18 expression are associated with response to antirejection therapy [29]. The discrepancy is probably explained by the fact that cellular rejection is essentially an inflammatory condition, and the severity or reversibility could understandably assessed by urinary NGAL and IL-18 expression.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…In contrast, our previous study in kidney transplant recipients found that urinary NGAL and IL-18 expression are associated with response to antirejection therapy [29]. The discrepancy is probably explained by the fact that cellular rejection is essentially an inflammatory condition, and the severity or reversibility could understandably assessed by urinary NGAL and IL-18 expression.…”
Section: Discussioncontrasting
confidence: 64%
“…The discrepancy is probably explained by the fact that cellular rejection is essentially an inflammatory condition, and the severity or reversibility could understandably assessed by urinary NGAL and IL-18 expression. We also previously found that urinary KIM-1 expression correlates with the rate of renal function decline in kidney transplant patients with acute renal dysfunction, irrespective to the kidney pathology [29]. In the present study, our duration of observation was short and we could not determine whether urinary KIM-1 provides the same long-term prognostic information for non-transplant patients with acute-on-chronic renal failure.…”
Section: Discussioncontrasting
confidence: 58%
“…In the past years, besides NGAL, several AKI and DGF biomarkers have been extensively investigated, including urinary KIM‐1, IL‐18, heat shock protein 72 (uHsp72), L‐FABP, calprotectin, CXCL9, CXCL10, CCL2, IL‐18, cystatin C, T‐cell immunoglobulin, and mucin domain‐3 (Tim‐3), tissue inhibitor of metalloproteinase 2 (TIMP‐2), insulin‐like growth factor‐binding protein 7 (IGFBP‐7) 57, 58, 59, 60, 61, 62, 63.…”
Section: Ngal and Other Candidate Biomarkers In Kidney Transplant Setmentioning
confidence: 99%
“…Natyvinių inkstų pažeidimų atveju padidėjusi KIM-1 koncentracija leidžia prognozuoti dializių poreikį, o pacientams po inksto transplantacijos KIM-1 koncentracijos nustatymas šlapi-me leidžia prognozuoti transplantato funkcijos blogėjimo greitį, tačiau neleidžia diferencijuoti skirtingų transplantato pažeidimo priežasčių [14].…”
Section: Su Neutrofilų Gelatinaze Asocijuotas Lipokalinas Ir Inkstų Punclassified